2018
DOI: 10.5603/fm.a2018.0010
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the relationship between the submandibular duct, lingual nerve and hypoglossal nerve

Abstract: Background: The aim of the study was to evaluate the relations between submandibular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The relationship of the LN with other structures such as the submandibular duct, the hypoglossal nerve, the inferior alveolar nerve, or the region of mandibular third molar have been described [ 21 , 27 , 28 ]. However, we have not been able to find in the literature studies with similar measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of the LN with other structures such as the submandibular duct, the hypoglossal nerve, the inferior alveolar nerve, or the region of mandibular third molar have been described [ 21 , 27 , 28 ]. However, we have not been able to find in the literature studies with similar measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Many anatomical studies of the lingual nerve, especially in the mandibular third molar or ramus region, have been investigated to avoid nerve injury during the extraction or dental anesthesia by many researchers 1,4–7 . However, the anatomical relationship between the lingual nerve and submandibular duct has not been investigated sufficiently 2,4,6,8 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the incidences of the lingual nerve below and above the submandibular duct were 99.4% and 0.6%, respectively. There was only 1 study that showed sides of the lingual nerve crossing above the submandibular duct 8 . Of the 8 sides, right and left sides were 4 and 4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The submandibular gland sits in a triangle bordered by the mandible and anterior and posterior digastric muscles, which drain to Wharton’s duct [ 2 ]. Variance in anatomy must be carefully considered, as understanding patterns of anatomy and relation of lingual nerve, hypoglossal nerve, and submandibular ducts is the most important factor in reducing nerve damage during surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%